The value of referral information and assessment - a cross sectional study of radiographers' perceptions - Catherine Chilute Chilanga; Hilde Merete Olerud; Kristin Bakke Lysdahl (BMC, 2022)
Abstract Background Radiology professionals are frequently confronted with referrals containing insufficient clinical information, which hinders delivery of safe and quality medical imaging services. There is however lack of knowledge on why and how referral information is important for radiographers in clinical practice. This study explores what purposes referral information is used/ useful for the radiographers, and the benefits of involving them in assessing referrals. Methods A cross sectional study was conducted of radiographers recruited through the International Society of Radiographers and Radiological Technologists (ISRRT) networks. A questionnaire was developed and distributed consisting of 5-point Likert scale questions on a) use/usefulness of referral information for 12 listed purposes and b) the benefits of radiographers assessing referrals for 8 possible reasons. The questionnaire was validated using a test-retest reliability analysis. Kappa values ≥0.6 were accepted. SPSS software was used for data analysis and chi-square tests to determine associations between using referral information and background variables. Results Total respondents were 279 (n = 233 currently in clinical practice and n = 46 in other positions). The participants in clinical practice ranked high all 12 listed purposes for use of referral information, and all except one received ≥60% 'frequent'/'very frequent' responses. Use for patient identification purposes received the highest score (97% 'frequently'/'very frequently' responses), followed by ensuring imaging of the correct body region (79% 'very frequently' responses). Radiographers not currently working in clinical practice ranked the 'usefulness' of listed items similarly. Significant associations between frequent use of referral information and education level were not observed, and only three items were significantly associated with modality of practice. All items on benefits of radiographers assessing referrals received ≥75% 'agree'/'strongly agree' scores. The items ranked highest were promotes radiographers' professional responsibility and improves collaboration with radiologists and referring clinicians, with 72 and 67% strongly agreed responses, respectively. Conclusion Radiographers use referral information frequently for several purposes. The referral information is needed for justifying and optimising radiological procedures, hence crucial for ensuring patient safety and high-quality services. This further emphasis why radiographers perceive several benefits of being involved in assessing the referral information.